Growth and mortality of coccolithophores during spring in a temperate Shelf Sea (Celtic Sea, April 2015). (October 2019) - Mayers, K.M.J.; Poulton, A.J.; Daniels, C.J.; Wells, S.R.; Woodward, E.M.S.; Tarran, G.A.; Widdicombe, C.E.; Mayor, D.J.; Atkinson, A.; Giering, S.L.C.
Highlights: Clear variation in coccolithophore growth and mortality rates throughout April. An Emiliania huxleyi bloom had exceptionally high rates of calcite production in April. Microzooplankton grazing exerted strong top-down control on coccolithophores. The fate of grazed calcite (dissolution or export) is an unknown but key consideration. Abstract: Coccolithophores are key components of phytoplankton communities, exerting a critical impact on the global carbon cycle and the Earth's climate through the production of coccoliths made of calcium carbonate (calcite) and bioactive gases. Microzooplankton grazing is an important mortality factor in coccolithophore blooms, however little is currently known regarding the mortality (or growth) rates within non-bloom populations. Measurements of coccolithophore calcite production (CP) and dilution experiments to determine microzooplankton (≤63 µm) grazing rates were made during a spring cruise (April 2015) at the Central Celtic Sea (CCS), shelf edge (CS2), and within an adjacent April bloom of the coccolithophore Emiliania huxleyi at station J2. CP at CCS ranged from 10.4 to 40.4 µmol C m −3 d −1 and peaked at the height of the spring phytoplankton bloom (peak chlorophyll- a concentrations ∼6 mg m −3 ). Cell normalised calcification rates declined from ∼1.7 to ∼0.2 pmol C cell −1 d −1, accompanied by a shift from a mixed coccolithophore species community to one dominated by the more lightly calcified species E. huxleyi and Calciopappus caudatus . At the CCS, coccolithophore abundance increased from 6 to 94 cells mL −1, with net growth rates ranging from 0.06 to 0.21 d −1 from the 4th to the 28th April. Estimates of intrinsic growth and grazing rates from dilution experiments, at the CCS ranged from 0.01 to 0.86 d −1 and from 0.01 to 1.32 d −1, respectively, which resulted in variable net growth rates during April. Microzooplankton grazers consumed 59 to >100% of daily calcite production at the CCS. Within the E. huxleyi bloom a maximum density of 1986 cells mL −1 was recorded, along with CP rates of 6000 µmol C m −3 d −1 and an intrinsic growth rate of 0.29 d −1, with ∼80% of daily calcite production being consumed. Our results show that microzooplankton can exert strong top-down control on both bloom and non-bloom coccolithophore populations, grazing over 60% of daily growth (and calcite production). The fate of consumed calcite is unclear, but may be lost either through dissolution in acidic food vacuoles, and subsequent release as CO2, or export to the seabed after incorporation into small faecal pellets. With such high microzooplankton-mediated mortality losses, the fate of grazed calcite is clearly a high priority research direction.